Manajemen Kesiswaan dalam Meningkatkan Prestasi Akademik dan Non-Akademik Siswa di SMP Muhammadiyah 1 Simpon dan SMPIT Nur Hidayah Surakarta - Hibatulloh, Syamsudin Nawwar; Narimo, Sabar; Shobahiya, Mahasri (Universitas Hamzanwadi, 2026)
The purpose of this study is to explore and explain the application of student management strategies in supporting academic and non-academic success at SMP Muhammadiyah 1 Simpon Surakarta and SMPIT Nur Hidayah Surakarta. Employing a qualitative methodology, the research is grounded in a phenomenological field study approach. Data were gathered through a combination of direct observations, semi-structured interviews, and document analysis. Data analysis follows the interactive model proposed by Miles and Huberman, which includes three essential phases: data reduction, data display, and conclusion drawing. To ensure the reliability and validity of the findings, the research incorporates triangulation methods involving both different techniques and multiple data sources. Findings reveal that both schools implement a well-organized student management framework encompassing planning, execution, and evaluation processes. The planning phase involves activities such as organizing the New Student Admission Committee (PPDB), selecting new students, and conducting talent and interest development programs. During the implementation phase, schools run extracurricular activities, character education initiatives, and various academic support programs. Evaluation is performed regularly through coordination meetings, achievement tracking, and the use of digital tools like Google Forms for self-assessment and reflection. This research concludes that integrated and adaptive student management significantly enhances student motivation, academic outcomes, and personal development. Despite contextual differences between the two institutions, both have effectively adopted management strategies tailored to student needs. The study highlights the critical role of aligning educational management practices with individual student development to establish a well-rounded and impactful educational experience